Mr. Putter & Tabby : See the stars - Rylant, Cynthia; Howard, Arthur (Orlando, Fla. : Harcourt, 2007)
Mr. Putter and Tabby find they are not the only ones awake when they go for a walk at midnight to cure Mr. Putter's pineapple-jelly-roll-induced insomnia.
Horn Book
School Library Journal starred
2.7
K-3.
K-3
Keywords: Cats -- Juvenile fiction; Neighborliness -- Juvenile fiction; Night -- Juvenile fiction; Putter, Mr. (Fictitious character) -- Juvenile fiction; Tabby (Fictitious character : Rylant) -- Juvenile fiction; Cats -- Fiction; Neighborliness -- Fiction; Night -- Fiction; Putter, Mr. (Fictitious character) -- Fiction; Tabby (Fictitious character : Rylant) -- Fiction; Cats -- Fiction; Neighborliness -- Fiction; Night -- Fiction; Putter, Mr. (Fictional character) -- Fiction; Tabby (Fictitious character : Rylant) -- Fiction; Readers (Elementary)